A gazdasági és társadalmi fejlődés elősegíti-e az emberek elégedettségének és boldogságának növekedését Kínában? - Kozjek-Gulyás, Anett (Távol-keleti Tanulmányok, 2018)
Whether a society is satisfied or not always provides important information on the operation of a country, from an economic and political perspective, among others. To what extent can we speak of healthy development of the society? How many in this society are dissatisfied with their situation and see the future prospects for themselves and their families hopeless? The answers to these questions can provide valuable feedback for the decision makers on the consequences of the decisions they made in the past and are making at present. This study utilizes the findings of empirical research carried out in January 2015 in Qinhuangdao 秦皇岛 as a starting point and aims to draw conclusions from the indicators of the level of satisfaction with the performance of the Chinese government – from the analysis of the indicators of happiness and satisfaction – to determine how much the subjective well-being of everyday Chinese people contribute to the long-term stability of the system of government and the undisturbed operation of China’s political system.